Maintaining financial stability in times of risk and uncertainty - Behl, Abhishek, 1987-; Nayak, Sushma, 1982- (IGI Global, 2019)
"This book explores perspectives on how risks and uncertainties affect the financial stability of individuals and institutions. It contains a serious study of the origins and effects of unpredictable events on individuals and on society and explores how to establish financial stability and security. It offers solutions to mitigate risk and achieve financial resilience under uncertainty"--